ANALISIS KEHILANGAN AIR DAN EFISIENSI SALURAN (STUDI KASUS SALURAN SEKUNDER BANTUL DI PEKALONGAN) - Ragil, Nafii; Wahyudi, Slamet Imam; Niam, M. Faiqun; Wahyudi, Rahma Sarah Wahyudi Sarah (Jurnal Teknik Sipil Giratory UPGRIS, 2025)
The Kaliwadas Irrigation Area is one of the irrigation networks under the authority of the Central Government (BBWS Pemali Juana) because it has an area of more than 3,000 Ha. Located in Pekalongan Regency, Central Java. Water intake from the Genteng River which connects the Kesesi Main Channel with the Bantul Secondary Channel. This study aims to analyze the Discharge Calibration, Water Loss, and Efficiency of the Bantul Secondary Channel from points B.Bt.1, B.Bt.2, and B.Bt.3. This research method, begins with the collection of secondary data obtained from the discharge data from BBWS Pemali Juana, previous measurements, primary data obtained from measurements using a current meter and the height of the threshold. Based on the study, it shows that the current meter and threshold have different discharge measurements. The primary data produced shows that the current meter produces the highest discharge of 2.19 m3 / s. The current meter has an average discharge of 0.89 m3 / s. Water loss is 25% with current meter and 31.6% with threshold, water loss in Bantul Secondary Channel is caused by leakage and physical condition of the channel. Larger flow distance, total channel efficiency decreases, reaching 86% to 76%, with efficiency threshold becomes 68%, percentage of this efficiency can be used for operation and maintenance basis.